КІБЕРЗЛОЧИННІСТЬ: ПОРІВНЯЛЬНИЙ АНАЛІЗ СУЧАСНОГО ІНФОРМАЦІЙНОГО ПРОСТОРУ (Computer systems and information technologies, 2021)
The burning problem of modern society - cybercrime, was considered in the article. In the process of studying cybercrimes and the mechanisms of protection against information security threats, the concept of cybercrime classification was carried out. The comparative analysis between the number of registered cyberattacks and losses from them was performed. The analysis of factual data was carried out, on the basis of which the table of cyberattacks quantity indicators, general losses was developed, and the cost of cyberattacks was calculated. The study provides recommendations for improving the reliability of information protection.